2012
DOI: 10.1073/pnas.1208689109
|View full text |Cite
|
Sign up to set email alerts
|

Physical manipulation of the Escherichia coli chromosome reveals its soft nature

Abstract: Replicating bacterial chromosomes continuously demix from each other and segregate within a compact volume inside the cell called the nucleoid. Although many proteins involved in this process have been identified, the nature of the global forces that shape and segregate the chromosomes has remained unclear because of limited knowledge of the micromechanical properties of the chromosome. In this work, we demonstrate experimentally the fundamentally soft nature of the bacterial chromosome and the entropic forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
278
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(291 citation statements)
references
References 60 publications
11
278
2
Order By: Relevance
“…1d). Although in line with some experimental observations (Pelletier et al 2012), this finding disagrees with evidence supporting the co-transcriptional translation, the mechanism by which ribosomes penetrate into the nucleoid and translate the mRNA transcripts while bound to the nucleoid.…”
Section: Computational Models Of the Genetic Materialssupporting
(Expert classified)
See 1 more Smart Citation
“…1d). Although in line with some experimental observations (Pelletier et al 2012), this finding disagrees with evidence supporting the co-transcriptional translation, the mechanism by which ribosomes penetrate into the nucleoid and translate the mRNA transcripts while bound to the nucleoid.…”
Section: Computational Models Of the Genetic Materialssupporting
(Expert classified)
“…Macromolecular crowders are unlikely to be the only determinants of chromosome compaction, as Shendruk et al (2015) concluded from observing a continuous rather than first-order transition as in experiments (Pelletier et al 2012). One such factor, i.e., DNA binding proteins (DBPs), has been studied by Brackley et al (2013b).…”
Section: Computational Models Of the Genetic Materialsmentioning
confidence: 99%
“…Indeed, the fast real-time compaction of chromosomes to native volumes [126] is observed in systems crowded by polymers. Our predictions are obtained for exponential phase of growth of E. coli, for which nucleoid is in an expanded state.…”
Section: Gene Expression In Living Cellsmentioning
confidence: 99%
“…Notably, the power law exponent B0.4 is not reproduced by standard polymer models 6 . The cytosol is a highly crowded environment, which promotes the chromosome to be (semi-)collapsed due to osmotic self-attraction 9,10 . However, in vivo the compacted chromosome (nucleoid) maintains a well-defined shape and tends to occupy a significantly smaller volume than the cell, likely a result of the activity of numerous DNA-associated proteins with varying functionality [11][12][13][14] .…”
mentioning
confidence: 99%